Fear of missing out - McGovern, Kate (2019)
Astrid's cancer has returned. It's an "astrocytoma," a tumor in her brain. She hears about a radical technology called cryopreservation that may allow her to have her body frozen until a future time when-- and if-- a cure is available. With her boyfriend, Mohit, and her best friend, Chloe, Astrid goes on a road trip in search of that possibility. To see if it's real. To see if it's worth it. For fear of missing out on everything. -- adapted from jacket
Keywords: Terminally ill -- Juvenile fiction; Cancer -- Juvenile fiction; Choice (Psychology) -- Juvenile fiction; Cryonics -- Juvenile fiction; Brain -- Cancer -- Patients -- Family relationships -- Juvenile fiction; Fiction; Juvenile works; YOUNG ADULT FICTION / Social Themes / Death, Grief, Bereavement; Fiction